Arnold Bennett and the Pursuit of Knowledge. Issue 2 (17th February 2017) - Hudson, Brian J.
ABSTRACT: Long neglected by literary scholars, the prolific works of English novelist and journalist Arnold Bennett have been studied by researchers in many other fields. This essay examines Bennett's fiction and non-fiction to reveal his thoughts on the pursuit of knowledge and the purpose and value of education. It throws light on the character of one of England's most controversial writers and on English culture at a time of rapid social change. Schooled in his native Staffordshire, Bennett abandoned plans to become a solicitor and became a writer, achieving great success on both sides of the Atlantic. His writings express strong views on education, including its purpose, which he saw as a preparation for complete living. He believed that formal education failed miserably, and he strongly advocated self-education. Bennett's views on the pleasures of learning, the school curriculum, women's education, universities and the relationship between scholarship and art are discussed.